Diseño y construcción de un prototipo de eductor para la eliminación de la cavitación en bombas centrífugas. - Palma Jaramillo, José Alberto (2004)
The necessity of this investigation this given by the purpose of solving the problem cavitacional in the process of hydraulic transport of the water. The investigation this structured in introduction, five chapters, conclusions and recommendations. Establishing a design methodology taking in consideration the good parameters of operation and their geometric parameters, the good design of an eductor will be achieved. For the construction technology he/she intends the method for manual welding for Electric Arch (SMAW) and/or welding for Metallic Arch With protection with gas (GMAW) to be economically more capable. I attach to the design of the jet bomb we propose the construction of an installation semi - industrial of closed system which will be good to carry out activities practices and of investigation in the unit of mechanics of fluids or energy laboratory and fluids, what will help to the educational process.